The effects of connected lighting on lighting controls and design - Sabourin, Nicole Tan (Kansas State University, 2017)
The Internet of Things (IoT) is rapidly growing and is starting to be incorporated into commercial buildings. One of the ways that the IoT is being used in buildings is connected lighting, also referred to as smart lighting. Connected lighting allows for communication between the lighting system, people, the environment, and other devices. This paper will focus on connected lighting and its effect on lighting controls and design. The IoT is expected to see substantial growth in the next few years and the growth of connected devices will have a huge impact on the lighting industry as connected lighting systems will be installed in more commercial buildings. The shift to solid state lighting (SSL) in recent years has brought the transition from conventional lighting controls to connected lighting controls. For this shift to be successful, issues with interoperability, security and reliability will need to be overcome. Connected lighting systems on the market are using both wired and wireless technologies. Power over Ethernet (PoE) and wireless technologies such as ZigBee and Bluetooth Smart are currently being incorporated into connected lighting systems. The introduction of these technologies is changing the way that lighting control systems are designed and installed. Products such as fixture-integrated sensors and wireless devices are also being used in connected lighting systems. These products, along with the wired and wireless technologies, are changing lighting control system configurations. Lighting design will also be affected by connected lighting systems. New features including color-tunability and indoor positioning will be used to enhance the lighting system and improve occupant health. Also, energy code compliance will be easier since connected lighting controls will be mostly software-based and can be reprogrammed. Connected lighting systems will be integrated into other building systems such as heating, ventilating, and air conditioning systems or security systems and will also be used in a variety of applications. Connected lighting systems will greatly affect both lighting controls and design of lighting control systems. This paper introduces connected lighting and is intended for those who are not familiar with its design, applications, and implementation.
Keywords: Smart lighting; Intelligent lighting; Lighting controls; Lighting designConnected lighting